Economic−statistical design of Vp control schemes for joint monitoring of mean and variance in the presence of multiple assignable causes. Issue 4 (4th July 2018) - Tasias, Konstantinos A.; Nenes, George
ABSTRACT: This paper presents a new statistical process control model for the economic–statistical optimization of a Variable-Parameter ( Vp ) Shewhart control scheme for monitoring processes where multiple assignable causes may occur. The assignable causes affect not only the mean but also the variance of a specific quality characteristic by leading to progressive process deterioration. The contemporary occurrence of the assignable causes and the different corrective action for each assignable cause makes the proposed model more realistic. The operation of the proposed control scheme is stochastically modelled by means of the Markov chain theory. The design parameters vary to get an economic and statistical performance optimization of the control scheme. An extended numerical investigation is utilized to demonstrate the economic and statistical superiority of the proposed model against simpler approaches. An example from aviation industry is presented to illustrate the application of the model.